2016
DOI: 10.1002/slct.201601186
|View full text |Cite
|
Sign up to set email alerts
|

Enantio- and Diastereoselective Synthesis of β-Nitroalcohol via Henry Reaction Catalyzed by Cu(II), Ni(II), Zn(II) Complexes of Chiral BINIM Ligands

Abstract: Enantiopure Cu(II), Ni(II) and Zn(II) chiral complexes CuLR, CuLS, NiLR, NiLS, ZnLR and ZnLS were synthesised by using ligands LR and LS, which were derived from the (R)‐(+)‐1,1’‐Binaphthyl‐2,2′‐diamine or (S)‐(−)‐1,1’‐Binaphthyl‐2,2’‐diamine with pyridine‐2‐aldehyde. These six complexes are characterised and applied as a catalyst for asymmetric nitroaldol reaction. The enantiopure chiral ligand upon complexation transfers its chirality from ligand to metal and generate “Δ or Λ” chirality at the metal centre. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 127 publications
3
6
0
Order By: Relevance
“…The tetrahedrally coordinated Zn II indeed acts as a Lewis acid center by accepting the lone‐pair electrons of the oxygen atom of the aldehyde as well as the electron density of the nitro group of nitromethane (Scheme B). The catalytic activities and yields of the products obtained by employing the present compounds are comparable to those reported in the literature (Table ) . To investigate the possible reuse of the catalyst, we isolated the catalyst after reaction and re‐employed it in the same reaction for up to three cycles.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The tetrahedrally coordinated Zn II indeed acts as a Lewis acid center by accepting the lone‐pair electrons of the oxygen atom of the aldehyde as well as the electron density of the nitro group of nitromethane (Scheme B). The catalytic activities and yields of the products obtained by employing the present compounds are comparable to those reported in the literature (Table ) . To investigate the possible reuse of the catalyst, we isolated the catalyst after reaction and re‐employed it in the same reaction for up to three cycles.…”
Section: Resultssupporting
confidence: 78%
“…We desired to explore this reaction by employing the present compounds I–IV as heterogeneous catalysts. Previous studies suggested that the tetrahedral Zn 2+ ions may act as Lewis acid centers and catalyze this reaction . In the present study, all four compounds contain tetrahedral Zn II within the structure and it occurred to us that these compounds could also be active in the nitroaldol reaction.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…The most common approach to compounds 1 is represented by the enantioselective Henry (nitroaldol) reaction between aldehydes and nitromethane, which is catalysed by metal complexes or organocatalysts [1,[6][7][8][9][10][11][12][13][14][15][16].…”
Section: Scheme 1 Synthesis Of β-Amminoalcohols 2 Through β-Nitroalcmentioning
confidence: 99%
“…In this regard, many homo‐ and heteronuclear complexes that are reported for their selectivity, copper‐ and zinc‐based homodimers are found to be efficient. Keeping this in mind, aiming to develop a new chiral catalyst with an enhanced stereoselectivity and recyclability at ambient conditions, we have recently reported similar binuclear copper complexes and mononuclear zinc complexes as efficient catalysts with high yield, ee and recyclability. In the present manuscript, we report very simple and easy‐to‐synthesize binuclear chiral complexes, which are efficient at catalysing such desymmetric acylation reactions.…”
Section: Introductionmentioning
confidence: 99%